ECONOMIC GROWTH THAT IS BOTH SUSTAINABLE AND INCLUSIVE PROPELS PROGRESS, GENERATES DECENT EMPLOYMENT FOR EVERYBODY, AND RAISES LIVING STANDARDS (World Economics and Finance Bulletin, 2022)
Economic growth is a requirement for expanding productive employment; it is the outcome of increased employment and labor productivity. The goals of people in their working life are summed up by decent work. As a result, the pace of economic expansion establishes the absolute limit within which employment and labor productivity may expand. However, the pattern or form of growth is also important. Arguments for economic growth that is both sustainable and inclusive can propel progress, generate decent employment for everybody, and raise living standards are presented in this article.
Keywords: Decent Work; ILO; Economic Growth; Developing Countries